Rancang Bangun Sistem Pemantauan Tekanan dan Suhu Ban Berbasis Internet of Things dan Software Defined Radio - Briantoro, Hendy; Budikarso, Anang; Arifin; Moegiharto, Yoedy; Yanuar Hariyawan, Mohammad (Jurnal ELEMENTER (Elektro dan Mesin Terapan), 2024)
There are many motor vehicle accidents on the road, one of the causes being tire blowouts. These accidents occur because drivers continue to drive their vehicles even though the tire pressure and temperature exceed the specified threshold. To address this issue, there is a need for a tire pressure and temperature monitoring system that can be continuously monitored by the driver. If there is a malfunction in the monitoring device on the vehicle dashboard, the driver can be alerted by others who also monitor tire pressure and temperature information remotely. In this study, we developed a tire pressure and temperature monitoring system for vehicles that can be accessed remotely using Internet of Things (IoT) technology. Additionally, we utilized Software Defined Radio (SDR) technology for pressure and temperature data reading. This system successfully monitors tire pressure and temperature changes remotely via computer and smartphone. Based on the test results, the best standard deviation value for tire pressure is 3.54, while the best standard deviation value for tire temperature is 1.72